ROW SPACING EFFECTS ON RADIATION DISTRIBUTION, LEAF WATER STATUS AND YIELD OF SUMMER MAIZE - J. Q. Liu; M. D. Li; X. B. Zhou (Journal of Animal and Plant Sciences, 2016)
Different row spacing can affect the canopy structure, and then affect the environment of crop growth and the yield. The research aimed to investigate the effects of row spacing on light interception ratio and leaf water status of summer maize (Zea mays L.), and to select the reasonable planting pattern. The experiment comprised five planting population distribution patterns in the same plant population density (62500 plant/ha) in northern China from 2011 to 2013. The following row spacing × spacing between the plant schemes were used: 40 cm × 40 cm (RS40), 50 cm × 32 cm (RS50), 60 cm × 27 cm (RS60), 70 cm × 23 cm (RS70), and 80 cm × 20 cm (RS80). A significant negative correlation was observed between row spacings and leaf relative water content (LRWC), water potential (Ψ) and yield during 3 years. RS40 and RS50 had the high total photosynthetically active radiation (PAR) capture ratio (CR) and upper CR (>100 cm) than the others. The yield of RS50 was higher than the others during three years study. The narrow row spacing (RS40 and RS50) was beneficial to the CR of PAR, LRWC, and Ψ. However, compared with RS50, the RS40 could increase the evapotranspiration and decrease the lower-CR. So RS50 could be the reasonable row spacing of summer maize in Huang-huai-hai Plain in China.
Keywords: Zea mays L.; evapotranspiration; capture ratio; leaf water potential; leaf relative water content